The emerging approaches to settle strikes in China. (2nd October 2019) - Huang, Xiaoyu; Zhang, Lihua; Huang, Wei; Zhu, Jinqiang; Van Wart, Montgomery; Qin, Ge
ABSTRACT: This paper explores the dynamics of settling strikes in China since the 1990s within the current constraints of political resources and industrial-relations institutions. The regulation of labour relations in China has been strengthened, and the priorities of the party-state have shifted from stressing capital attraction to social stability. Labour shortages have tilted the power balance to be more in favour of workers. Employers can no longer rely solely on the endorsement of the local government in settling the strikes as they did in the 1990s. We conduct the case studies of strikes in two wholly foreign-owned enterprises and investigate how the two companies prevented and resolved the collective disputes of workers. We compare three waves of strikes in each of the two locations that occurred between 1994 and 2012. In both locations, employer responses have swung from passive to proactive coping and building trust. These inputs have played a decisive role in both the prevention and final resolution of conflicts over time. Our study revealed the complementary interactions between collective negotiation and HRM as an emerging effective approach in preventing and settling the strikes. Our study supports the current view that China's dispute-resolution system has evolved in the last two decades towards greater formalisation and institutionalisation.